Pengaruh Penerapan Konsep Ecopreneurship Pada Mata Kuliah Kewirausahaan Untuk Melatih Keterampilan Proses Sains Berwirausaha Mahasiswa Pendidikan IPA ULM - Mayka Lara Santi; Rizky Febriyani Putri; Sauqina . (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
The aim of this research is to explore the influence of science process skills in the context of student entrepreneurship through the application of the ecopreneurship concept in learning entrepreneurship courses among science education students at Lambung Mangkurat University (ULM). Using a quantitative approach by applying a quasi-experimental method and using a one group pretest posttest design where ULM Science Education students act as research subjects. Sample selection used purposive sampling technique. Analyzed using the N-Gain statistical method, Paired Sample t-test, and correlation test to identify relationships between variables and to assess the extent of the influence of applying the ecopreneurship concept in training students' entrepreneurial KSP (science process skills). The results of the analysis show that the application of the ecopreneurship concept has a significant influence on students' entrepreneurial science process abilities, as seen from the significance value (2-tailed) of 0.000, which is below the limit of 0.05, carried out through the distribution of questionnaires for all indicators of science process skills, showing that the application of the ecopreneurship concept in learning not only improves the students' learning process, but also prepares them to become entrepreneurs who are responsible and oriented towards environmental sustainability.